الإمام المصلح عبد الحميد بن باديس: حياته وجهوده التربوية= al-Imam al-muslih 'Abd al-Hamid ibn Badis: hayatuhu wa-juhuduhu al-tarbawiyah - 'Abd al-'Alali, Bay Zakub; Solihin, Sohirin Mohammad (International Islamic University Malaysia, 2015)
ImÉm ‘Abd al-×amÊd ibn BÉdÊs is an Algerian scientist, and eminent social, religious, political and educational reformer. He lived fifty years in the twentieth century. He was born in 1889 and died in 1940, and lived during the French occupation that attempted to distort and undermine the foundations of the Algerian nation by destroying its history, identity, culture, and religious and linguistic unity. Ibn BÉdÊs pursued an educational approach to face the brutal French occupation on several fronts, including journalism, education, civil associations, politics, etc. This paper highlights the role of ‘Abd al-×amÊd ibn BÉdÊs in the advancement of the Algerian nation toward better education and a happier life. The paper begins with a brief canvas of the difficult times in which Ibn BÉdÊs lived, and the negative effects of the brutal French occupation from political, economic, social, cultural and religious angles, besides highlighting the life of Ibn BÉdÊs, his education and his local and international travels. The focus of this research is an in-depth examination of Ibn BÉdÊs’ social and educational efforts that consumed much of his daily routine: journalism, and education.